Prevalence and Determinants of Adequate Compliance with Antenatal Care in Peru - Tello-Torres, Cesar; Hernández-Vásquez, Akram; Dongo, Karla F.; Vargas-Fernández, Rodrigo; Bendezu-Quispe, Guido (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective To determine the adequacy of compliance with antenatal care (ANC) by pregnant women in Peru and to identify the associated factors.Methods An analytical cross-sectional study of data from the 2019 Peruvian Demographic and Family Health Survey (Encuesta Demográfica y de Salud Familiar, ENDES, in Spanish) was conducted. The dependent variable was adequate compliance with ANC (provided by skilled health care professionals; first ANC visit during the first trimester of pregnancy; six or more ANC visits during pregnancy; ANC visits with appropriate content) by women aged 15 to 49 years in their last delivery within the five years prior to the survey. Crude and adjusted prevalence ratios and their 95% confidence intervals were calculated using a log-binomial regression model.Results A total of 18,386 women were analyzed, 35.0% of whom adequately complied with ANC. The lowest proportion of compliance was found with the content of ANC (42.6%). Sociodemographic factors and those related to pregnancy, such as being in the age groups of 20 to 34 years and 35 to 49 years, having secondary or higher education, belonging to a wealth quintile of the population other than the poorest, being from the Amazon region, not being of native ethnicity, having a second or third pregnancy, and having a desired pregnancy, increased the probability of presenting adequate compliance with ANC.Conclusion Only 3 out of 10 women in Peru showed adequate compliance with ANC. Compliance with the content of ANC must be improved, and strategies must be developed to increase the proportion of adequate compliance with ANC.
Keywords: prenatal care; health surveys; cross-sectional studies; quality of health care; maternal health; maternal health services; Peru